Perintisan Sekolah Komunitas Muhammadiyah untuk Pekerja Migran Indonesia (PMI) di Balad, Yordania - Muh Nur Rochim Maksum; alfan rifai (Universitas Muhammadiyah Surakarta, 2024)
Pekerja Migran Indonesia (PMI) or Indonesian Migrant Workers in Jordan face many problems, especially educational problems, this happens because the majority of them only graduated from elementary school (SD) and do not have sufficient religious knowledge. To overcome this problem, pengabdian kepada masyarakat kemitraan international or the Community Service International Partnership (PKM-KI) team at Muhammadiyah University of Surakarta (UMS) runs Muhammadiyah Community School project for PMI in Balad Jordan. Various institutions from Jordan, such as PCIM Jordan, PPI Jordan, and the Indonesian Embassy in Jordan, collaborated this project. A Situation analysis was carried out through interviews with partners to start the project planning process. The implementation stage involved determining basic school values, creating learning materials, and training for participants. The results of the evaluation, which was conducted through direct interviews and observations, showed improvements in PMI's social-emotional and religious skills, as well as more ties and awareness of the importance of education. To ensure continuity of learning and evaluation of progress, the mentoring stage was carried out periodically via the Whatsapp group. Therefore, the Muhammadiyah community school pilot project was successful in addressing PMI education problems in Jordan through a collaborative approach between universities, community organizations and government institutions. This shows that community education is a relevant solution to improve the welfare and quality of life of PMI. Thus, through a collaborative approach between community organizations, universities and government institutions, the pioneering Muhammadiyah community school in Balad Amman Jordan has succeeded in overcoming the educational challenges faced by PMIs in Jordan. This shows the potential for community education to be a concrete solution that is relevant to improving the welfare and quality of life of PMI.